Permasalahan Penerapan Administrasi Bagi Guru Kelas Sekolah Dasar - Andri Wicaksono; Ali Imron Al Ma'ruf; Fitri Puji Rahmawati (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
In carrying out learning activities in class, a teacher is obliged to carry out learning administration. Learning administration equipment is very much needed for classroom learning. The implementation of teacher administration has become a polemic in schools. Teachers still experience problems in completing administration and carrying out administrative filling. This research aims to describe the problems of implementing class teacher administration at SD Negeri 1 Jatiroto. This research uses a case study perspective with a qualitative approach. This research uses data collection techniques in the form of interviews, observation and documentation. After the data acquisition process is complete, the data analysis techniques used are data reduction, data presentation, and data verification or drawing conclusions. Testing the validity of the data uses triangulation techniques, namely source triangulation, technique triangulation, and time triangulation. The results of the research show that class teachers have not carried out their administrative duties well because there are still several administrative tasks that have not been completed, such as determining KKM, improvement questions, enrichment questions and question grids. Apart from that, class teachers experience several obstacles in implementing class teacher administration, namely limited time, lack of effective archiving media, forgetfulness in archiving. Thus, to meet administrative needs and overcome obstacles to implementing administration, a more efficient form of administration is needed.